PEMBEBANAN MODEL PELAT SKALA KECIL PERKERASAN KAKU (RIGID PAVEMENT) DI ATAS TANAH PASIR - Setiawan, Bambang; Purwana, Yusep Muslih; Dananjaya H.I, Raden Harya (Jurnal Riset Rekayasa Sipil, 2023)
Road infrastructure issues need great attention, considering that this was a link and a cross-economy between one region and another. Damage to the pavement (pavement) would have fatal consequences for the development of an area and an increase in financial needs. Therefore, it was necessary to strengthen a solid road body so that it was able to strengthen the road and be comfortable for traffic loads to pass. Damage to the road body was a major concern in road maintenance efforts. This was due to several very complex problems in terms of the materials used, work implementation, traffic loads passing through the road body, and existing natural conditions. This research studies and analyses the behavior of dynamic-loaded rigid pavements. This load was a traffic load model, and the behavior was reviewed in a small-scale laboratory model. The expected result was to know the model’s behavior with and without rigid pavement reinforcement on both sandy and soft soils, namely in the form of analysis and the ability of the reinforcement to accept traffic loads. This research showed that the plate test model shows that multiple plate thickness supports plate stiffness. The cakar reinforcement plate affected the stiffness of the plate. The deflection value due to loading on the 3-layer plates (6.3 mm thick) was comparable to the 1-layer plate (2.1 mm) with cakar. FEM analysis can be performed to predict deflection due to loading in the center of the plate, and this value was very close to the results of the laboratory small-scale loading test. The CBR value used to calculate the deflection was closest to the real condition, namely the value before loading 0.2 kN and after loading 0.8 kN.